The Land War in Ireland famine, philanthropy and moonlighting - Geary, Laurence M. (Cork University Press, 2023)
"This book addresses perceived lacunae in the historiography of the Land War in late nineteenth-century Ireland, particularly deficiencies or omissions relating to famine, humanitarianism and the activities of agrarian secret societies, commonly referred to as moonlighting. The famine that afflicted the country in 1879-80, one generation removed from the catastrophic Great Famine of the 1840s, prompted different social responses. The wealthier sectors of society, their consciousness and humanitarianism awakened, provided the bulk of the financial and administrative support for the famine-stricken peasantry. Others, drawn from the same broad social stratum as the latter, vented their anger and frustration on the government and the landlords, whom they blamed for the crisis. The concern of marginal men and women for the welfare of their less fortunate brethren was not so much the antithesis of altruism, as a different, more rudimentary way of expressing it
Includes bibliographical references (pages 231-292) and index
Keywords: Geschichte 1879-1880; Hungersnot; Grundeigentum; Geschichtsschreibung; Agrargesellschaft; Irland; Land League (Ireland); Land tenure / Ireland / History / 19th century; Famines / Ireland / History / 19th century; Humanitarian assistance / Ireland / History / 19th century; Ireland / History / 1837-1901; Propriété foncière / Irlande / Histoire / 19e siècle; Famines / Irlande / Histoire / 19e siècle; Aide humanitaire / Irlande / Histoire / 19e siècle; Irlande / Histoire / 1837-1901